"Povo de ilha" dinâmica territorial, identidade e tradição de conhecimento no Porto do Capim- PB - Assad, Patricia (2017)
This work investigates the processes of constitution of the Porto do Capim community and the relations that its inhabitants develop with varied elements in the existing environments, considering the social and ecological context and territorial dynamics involved in the construction of this place. In this way, it seeks to understand the processes involved in the constitution of a tradition of knowledge, in the terms proposed by Fredrik Barth, that composes the universe of material and moral references of the Porto do Capim community. The community of Porto do Capim is located on the right bank of the river Sanhauá, one of the tributaries of the Paraíba do Norte river, birthplace of the city of João Pessoa, and arises from the occupation of that area, around the 1950s, especially by families of fishermen and shellfish collectors who lived in nearby neighborhoods or on the surrounding river islands, as well as Port workers on the site. Since the end of the 1990s these inhabitants have been living with the threat of being removed from the place, for the construction of works and projects aimed at tourism. The question then arises that more than the practices and forms of use of the local territory, it is possible to comprehend more broadly an identity and a tradition of knowledge that comes from the experiences in the estuary of the Paraíba do Norte river, as revealed in this research. And that, in this case, it is linked to the various contexts that involve the use, occupation and significance of these spaces. Based on the present research, it could be observed that the identity frameworks, the ways of interpreting the world and being in it, together with a moral compound that accompanies them, that is, the cultural baggage of an individual is constructed in a procedural way, from the interpretations and experiences lived and their interactions in the environments.